Similar long‐term efficacy of dual therapy containing raltegravir and a boosted protease inhibitor versus standard triple therapies in pretreated HIV‐1‐infected patients in a retrospective, real‐life cohort of 14 years. Issue 9 (3rd July 2018) - Krznaric, I; Bickel, M; Carganico, A; De Leuw, P; Haberl, A; Knecht, G; Koegl, C; Lauscher, P; Schüttfort, G; Stephan, C; Wolf, E; Wolf, T
Abstract : Objectives: Raltegravir is used in many antiretroviral combinations, but its use in treatment‐experienced patients without knowledge of baseline resistance is discussed controversially as a number of comparative studies have shown a higher rate of virological failure. However, it has been used frequently for the management of treatment failure, as it was the first integrase inhibitor to become available, and thus offered new options for patients with multiple resistance. The strategic use of raltegravir in this setting is examined in this study. Methods: In order to examine the efficacy of raltegravir in second and later lines of antiretroviral combinations, data for 740 patients from three clinical cohorts were analysed with a focus on the combinations that were used. These were stratified into the combination of two nonnucleoside reverse transcriptase inhibitors and raltegravir (2NRTIs + RAL), the combination of a boosted protease inhibitor and raltegravir (bPI + RAL), and other raltegravir‐containing combinations. Results: The overall rate of virological suppression to < 50 HIV‐1 RNA copies/mL was 69.5%. Although the baseline rate of virological suppression was higher for 2NRTIs + RAL than for the other strata, the outcomes were similar for all three groups at weeks 24, 48, 72 and 96. Conclusions: These data indicate that, in a real‐life setting, raltegravir can be used with a high virological success rate in treatment‐experienced patients, and that the different combinations analysed (2NRTIs + RAL, bPI + RAL and others) show comparable rates of virological suppression.